Dragon flight - George, Jessica Day, 1976- (Bloomsbury U.S.A. Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2008)
Young seamstress Creel finds herself strategizing with the dragon king Shardas once again when a renegade dragon in a distant country launches a war against their country, bringing an entire army of dragons into the mix.